En medio de espacios cambiantes: movilidad política y geográfica de un activista en el norte de México y el suroeste estadounidense, 1865-1932 - Vázquez Valenzuela, David Adán (El Colegio de México, A.C., 2023)
This article analyzes the life of Salvador Medrano, a migrant worker and secondary figure who lived through the transition from the Porfiriato to the Mexican Revolution. It argues that it is valuable to explore his experiences because they cover a period of changes in Mexican and U.S. history and help us understand the way in which a large area of both countries underwent a transformation at the end of the nineteenth century and beginning of the twentieth. Over the course of his life, Medrano lived in a variety of work destinations in northern Mexico and the southwestern U.S. that had emerged thanks to growing capital investments. He also participated in a political revolt that attempted to overthrow Díaz in 1893, and in the twentieth century, joined the Mexican Liberal Party and the Mexican Revolution.